Mannan-binding lectin suppresses growth of hepatocellular carcinoma by regulating hepatic stellate cell activation via the ERK/COX-2/PGE2 pathway. (1st February 2019) - Li, Junru; Li, Huifang; Yu, Yu; Liu, Yan; Liu, Yunzhi; Ma, Qiang; Zhang, Liyun; Lu, Xiao; Wang, Xiang-yang; Chen, Zhengliang; Zuo, Daming; Zhou, Jia
ABSTRACT: Mannan binding lectin (MBL), initially known to activate the complement lectin pathway and defend against infection, was recently shown to be potentially involved in the development of several types of cancer; however, its exact role in cancers, especially its effect on tumor microenvironment remain largely unknown. Here, using a murine hepatocellular carcinoma (HCC) model, we showed that MBL was a component of liver microenvironment and MBL-deficient (MBL –/– ) mice exhibited an enhanced tumor growth compared with wild-type (WT) mice. This phenomenon was associated with elevation of myeloid derived suppressed cells (MDSCs) in tumor tissue of MBL –/– mice. MBL deficiency also resulted in an increase of activated hepatic stellate cells (HSCs), which showed enhanced cyclooxygenase-2 (COX-2) expression and prostaglandin E2 (PGE2 ) production. Pharmacological inhibition of COX-2 in vivo partially abrogated the MBL deficiency-promoted tumor growth and MDSC accumulation. Mechanistic studies revealed that MBL could interact directly with HSCs and inhibit HCC-induced HSCs activation via downregulating the extracellular signal-regulated kinase (ERK)/COX-2/PGE2 signaling pathway. Furthermore, MBL-mediated suppression of HCC is validated by administration of MBL-expressing, liver-specific adeno-associated virus (AAV), which significantly inhibited HCC progression in MBL –/– mice. Taken together, these data reveal that MBL may impact on tumor development by shaping the tumor microenvironment via its interaction with the local stromal cells, and also suggests its potential therapeutic use for the treatment of HCC.